2015
DOI: 10.1155/2015/839518
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Platform Evaluation of Commercial Real-Time SYBR Green RT-PCR Kits for Sensitive and Rapid Detection of European BatLyssavirusType 1

Abstract: This study evaluates the performance of five two-step SYBR Green RT-qPCR kits and five one-step SYBR Green qRT-PCR kits using real-time PCR assays. Two real-time thermocyclers showing different throughput capacities were used. The analysed performance evaluation criteria included the generation of standard curve, reaction efficiency, analytical sensitivity, intra- and interassay repeatability as well as the costs and the practicability of kits, and thermocycling times. We found that the optimised one-step PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
2
21
1
Order By: Relevance
“…2012; PICARD-MEYER, 2015). In this study, the kit I was faster, with better melting curves showing better performance and was used to evaluate the analytical sensitivity of Systems A and B.…”
Section: Resultsmentioning
confidence: 99%
“…2012; PICARD-MEYER, 2015). In this study, the kit I was faster, with better melting curves showing better performance and was used to evaluate the analytical sensitivity of Systems A and B.…”
Section: Resultsmentioning
confidence: 99%
“…Since the clinical diagnosis of rabies is difficult and poorly reliable, especially if the history of a bite by a rabid animal is not present (15); in these cases, specialized diagnosis of rabies is required. The failure of routine diagnostic are not in molecular methods.…”
Section: Discussionmentioning
confidence: 99%
“…For that study, HPV was selected to generate HPV RNA transcript. We selected two different commercial cDNA synthesis kits for detecting HPV and evaluated the results using efficiency and R 2 as shown in a paper [28]. Results showed that efficiency (%) was between 90%∼110%…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR for HPV screening test is performed after RNA extraction, complementary DNA (cDNA) synthesis, and amplification of cDNA [25][26][27]. Real-time PCR gene expression can depend on efficiency (%) of complementary DNA synthesis even if total RNA is extracted efficiently [28].…”
Section: Introductionmentioning
confidence: 99%